Perceived barriers to the movement of goods in Canada: A grounded theory investigation. (August 2022) - Sears, Sean; Moataz, Mohamed; Ferguson, Mark; Razavi, Saiedeh; Páez, Antonio
Abstract: This paper investigates stakeholder's perspectives about freight congestion in Canada's major metropolitan regions. Interviews with 28 Canadian stakeholders from different sectors are analyzed using Strauss/Corbin extended approach of symbolic interactionism with the objective of producing an explanatory theory to identify barriers to freight in Canada. By integrating emergent categories with a structured framework of theoretical propositions, we are able to offer insights to understand the perceived barriers to goods movement in the Canadian landscape, as well as to detail a framework of interventions to improve freight mobility. In total, 50 themes emerged as barriers to the movement of goods, which were grouped into nine subcategories, and four overarching categories which broadly frame the issues of goods movements as relating to high infrastructure utilization ( Infrastructure Demand Outstripping Supply ), the cost impacts of diminishing reliability of distribution ( Physical Distribution Headwinds Impeding Commerce ), rapidly growing regions and ineffective or absent policy support ( Urgent Regulatory Encumbrances ), and a lack of a robust data collection, analysis, and information sharing framework ( Information and Data Management Complexities ). These categories were considered in the frame of addressing goods movement barriers and were argued to be influenced by factors of cost, political risk, implement-ability, and maintainability. A framework was developed identifying four high-level interventions: data and knowledge mobilization; public-private collaborative freight evaluations; government funding and political support; and, capacity alterations: improvements and expansions. The key concepts of the framework are to collect and analyze data to inform public-private stakeholder evaluations of policy interventions, with government funding to support both knowledge generation efforts, policy actions and capacity investments. There is a significant need to expand data collection and information sharing, focus infrastructure investments on public transit and intermodal accessibility, and integrated policy development towards transportation and land use planning to address the physical and policy barriers affecting freight mobility and congestion. The emergent theory is contrasted with selected global regions to assess generalizability and the relevance of international perspectives to the Canadian environment.